Project management in central banks - Milena Vučinić; Radoica Luburić (Journal of Central Banking Theory and Practice, 2023)
In this ever-changing environment of technological innovations central banks are strongly committed to fulfilling their key objectives of preserving monetary and financial stability, but also make efforts to adapt to new market requirements. On the path of technological transformation of financial systems, central banks face many challenges stemming from, inter alia, new less regulated and decentralized financial innovative services, cyberattacks, and endangered cyber security. Central banks need strong project management to successfully address these processes and that should be done in line with the highest international standards. The paper analyses the implementation of project management in central banks according to the international standards. The authors present possible division of roles and responsibilities in the project organization structure in central banks based on these international standards. The standardized integrated project management activities and associated practices are described and presented in the context of project management in central banks. The authors conclude that the application of international standards is crucial for successful project management in central banks in order to ensure that the projects are implemented on time and within the envisaged scope and budget, thereby ensuring high quality results, efficient deployment of human resources, benefits realization and value creation for the organization.
Keywords: E58; O30; 330; central bank; project management; international standards